2021
DOI: 10.1016/j.diabres.2021.108760
|View full text |Cite
|
Sign up to set email alerts
|

Combined lifestyle factors and the risk of LADA and type 2 diabetes – Results from a Swedish population-based case-control study

Abstract: We investigated the risk of latent autoimmune diabetes in adults (LADA) and type 2 diabetes in relation to a healthy lifestyle, the proportion of patients attributable to an unhealthy lifestyle, and the influence of family history of diabetes (FHD) and genetic susceptibility. Methods:The population-based study included incident LADA (n = 571), type 2 diabetes (n = 1962), and matched controls (n = 2217). A healthy lifestyle was defined by BMI < 25 kg/m 2 , moderate-to-high physical activity, a healthy diet, no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…In such instances, results from the most recent publication are presented, and if there were separate effect estimates for the same exposure in different publications, those were pooled to get an overall estimate of the associations. To address the heterogeneity of LADA, some studies reported results separately for LADA with high vs. low GADA levels, divided by the median ( 36 , 39 42 , 49 ). These subgroups will be referred to as LADA high and LADA low .…”
Section: Lifestyle or Environmental Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…In such instances, results from the most recent publication are presented, and if there were separate effect estimates for the same exposure in different publications, those were pooled to get an overall estimate of the associations. To address the heterogeneity of LADA, some studies reported results separately for LADA with high vs. low GADA levels, divided by the median ( 36 , 39 42 , 49 ). These subgroups will be referred to as LADA high and LADA low .…”
Section: Lifestyle or Environmental Factorsmentioning
confidence: 99%
“… Lifestyle factors and LADA-findings from observational studies. Relative risk estimates extracted from references ( 28 , 36 , 39 47 ). …”
Section: Lifestyle or Environmental Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In such instances, results from the most recent publication are presented, and if there were separate effect estimates for the same exposure in different publications, those were pooled to get an overall estimate of the associations. To address the heterogeneity of LADA, some studies reported results separately for LADA with high vs. low GADA levels, divided by the median (36,(39)(40)(41)(42)49). These subgroups will be referred to as LADA high and LADA low .…”
Section: Literature Searchmentioning
confidence: 99%